Influence of double solution treatment on hardness in 17-4 pH steel - Roman Sowa; Wojtan Magdalena Parlinska; Sebastian Arabasz; Andrzej Dziedzic; Irena Dul (Zaštita Materijala)
The investigated material is a corrosion-resistant, Cu precipitation hardened steel 17-4PH, which undergoes a macroscopic contraction, as a result of applying the following heat treatment: double solution treatment at 1028°C for 1 h (condition A), ageing at 540°C for 4 h (condition H1025). The second solution treatment at 1028°C was found to eliminate the retained austenite, being the evidence of a completely finished martensitic transformation. Indeed, the only phase identified in all samples was fcc lath marten site exhibiting a parallel striped structure. Unfortunately, this additional heat -treatment operation leads likewise to significant and irregular grain growth, which consequently causes a drop in material hardness. In addition to the martensitic phase, in the unaged samples, a δ-ferrite phase could be identified by TEM and electron diffraction, which is favorable for ductility and toughness of the material. In all samples, non-coherent fcc-NbC precipitates identified by electron diffraction and EDX mapping having sizes up to 70 nm were found.